STUDY OF VERTEBRATE DIVERSITY AT LAL SUHANRA NATIONAL PARK, - B. N. Khan; R. Ahmad; Z. Ali; R. Yasmeen; M. Azhar; F. Abid; S. Mehmood; H. Raza (Journal of Animal and Plant Sciences, 2018)
The field surveys of Lal Suhanra National Park ( LSNP) Bahawalpur were conducted to study its vertebrate diversity between October and December 2015. The study was commenced to determine the status of fauna of national park, diversity indices and environmental intimidations to their protection. The data was collected by point count method. The fauna observed there included 17 species of mammals including Asiatic wolf that is endangered. Five species of amphibians and 27 species of reptiles were found there. Among reptiles, Chitra indica is endangered. The results of study showed that maximum account of 7443 birds of 74 species belong to 35 families and representative of 16 orders were witnessed during the study. The seasonal distribution pattern of birds shown that year around resident were 76%, 7% were summer breeders, 4% were passage migrants while 5% were uncommon and 8% were common winter migrants. Hunting, deforestation, wood logging, disturbance by human activities and habitat loss are the major threats for wild animals at LSNP. Alteration in natural lake and their flows for recreational purposes is also a major threat. Proper attention should be given to existing habitat of study area for conservation of unique fauna of this biosphere reserve. Lal Suhanra Nartional Park (LSNP) ; in 1972,
Keywords: National park; Vertebrate diversity; Lal Suhanra; Habitat loss.